2018
DOI: 10.1080/23251042.2018.1463488
|View full text |Cite
|
Sign up to set email alerts
|

Organizing international experts: IPBES’s efforts to gain epistemic authority

Abstract: What role do organizational preconditions play in the constitution of expertise? This is the guiding question for this paper, which studies how expertise is shaped in the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES). By organizing the world's experts on biodiversity, IPBES sets out to produce policy-relevant knowledge. However, in contrast to many other international expert bodies such as the IPCC, IPBES assesses not only scientific knowledge, but also other forms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Instead, he highlighted the need to acknowledge nonutilitarian views of nature, the concepts of Pachamama and buen vivir, and the fact that Nature has rights of its own. His statement was a key structural moment of contestation, which anticipated a shift in the wordingfrom 'ecosystem services' to 'nature's contributions to people'a development that Gustafsson and Lidskog (2018) have described as the IPBES' struggle to gain and sustain 'epistemic authority´. As a result of this alteration of meaning, the legitimacy of interdisciplinarity and transdisciplinarity within the IPBES and the role of traditional knowledge in its assessment reports increased (Vadrot, Jetzkowitz, and Stringer 2016;Vadrot et al 2018; Díaz-Reviriego, Turnhout, and Beck 2019).…”
Section: Collaborative Event Ethnography: Observing Contestation In 'mentioning
confidence: 99%
“…Instead, he highlighted the need to acknowledge nonutilitarian views of nature, the concepts of Pachamama and buen vivir, and the fact that Nature has rights of its own. His statement was a key structural moment of contestation, which anticipated a shift in the wordingfrom 'ecosystem services' to 'nature's contributions to people'a development that Gustafsson and Lidskog (2018) have described as the IPBES' struggle to gain and sustain 'epistemic authority´. As a result of this alteration of meaning, the legitimacy of interdisciplinarity and transdisciplinarity within the IPBES and the role of traditional knowledge in its assessment reports increased (Vadrot, Jetzkowitz, and Stringer 2016;Vadrot et al 2018; Díaz-Reviriego, Turnhout, and Beck 2019).…”
Section: Collaborative Event Ethnography: Observing Contestation In 'mentioning
confidence: 99%
“…Research into intergovernmental assessment bodies, like IPBES, has focused on sociohistorical emergence (Charvolin and Ollivier 2017;Granjou et al 2013;Vadrot 2014aVadrot , 2014b; the relationship between science and politics (Brand and Vadrot 2013;Compagnon and LePrestre 2016;Gustafsson and Lidskog 2018;Hrabanski and Pesche 2016;Morin et al 2017;Turnhout et al 2014Turnhout et al , 2016; and the structural, geographical, and disciplinary makeup of the organization and its products (Duperray et al 2016;Esguerra et al 2017; Kovács and Pataki 2016;Montana 2017;Montana and Borie 2016;Oubenal et al 2017;Timpte et al 2018;Vadrot et al 2018aVadrot et al , 2018b. The intertwinement between science and politics, and how to characterize it, is a central scholarly focus in IPBES and IPCC scholarship (see, e.g., Haas 2004;Hoppe et al 2013;Miller 2004;Shackley and Wynne 1996;Skodvin 2000).…”
Section: Studying Intergovernmental Expert Bodiesmentioning
confidence: 99%
“…While so-called alternative forms of knowledge, often identified as indigenous and local knowledge (ILK), are not recognized as equivalent to scientific knowledge, they are increasingly shaping the outputs of both IPBES (Gustafsson and Lidskog 2018;Obermeister 2018;Tengö et al 2017) and CBD (Suiseeya 2014;Witter et al 2015). 2 Within IPBES, contestation over scientific framings, such as the use of "ecosystem services," has shaped the organization and its conceptual basis (Borie and Hulme 2015;Vadrot 2014aVadrot , 2014b, and the inclusion of ILK is now explicitly recognized within IPBES products (Díaz et al 2015(Díaz et al , 2018Pascual et al 2017).…”
Section: Bourdieu Knowledge and Global Environmental Ordermentioning
confidence: 99%
“…However, on an empirical level, previous research has shown how expertise is often identified through a combination of substantive and relational considerations (Lidskog and Sundqvist 2018). For example, to be an expert, there is often not enough for someone to simply hold specialized knowledge: the person also needs to be perceived by others as an expert (Gustafsson and Lidskog 2018). By making use of these two concepts, this paper's analysis study how the current organizational arrangements and structural preconditions of the IPCC and the IPBES implicitly define what constitutes expertise and how this comes to influence the creation of the next generation of experts by structuring the introduction of early career researchers.…”
Section: Theoretical Framework On Expertisementioning
confidence: 99%
“…Both the Intergovernmental Panel on Climate Change (IPCC) and the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES) were established as boundary organizations to create such constructive relations (cf. Guston 2000;UNEP 2010;Gustafsson and Lidskog 2018). By gathering, assessing, and communicating the world's expertise on climate change and the loss of biodiversity and ecosystem services, both the IPCC and the IPBES aim to be policy-relevant but not policy prescriptive.…”
Section: Introductionmentioning
confidence: 99%